Effects of a school teacher‐led 45‐minute educational program for mental health literacy in pre‐teens - Ojio, Yasutaka; Foo, Jerome Clifford; Usami, Satoshi; Fuyama, Taruto; Ashikawa, Megumi; Ohnuma, Kumiko; Oshima, Norihito; Ando, Shuntaro; Togo, Fumiharu; Sasaki, Tsukasa (Early intervention in psychiatry, 2019)
Aim A concise teacher-led program for mental health literacy (MHL), suitable for schools with tight schedules was developed, and its effects were examined in pre-teens. Methods Participants comprised 662 grade 5 to 6 students from nine Japanese elementary schools. The program consisted of a 45-minute session, delivered by school teachers using a 10-minute animated film. Program focuses included: mental health problems are common, can be associated with lifestyle and that seeking help from reliable adults is a key to finding solutions. Participants filled out self-report questionnaires before, immediately after and 3 months post-intervention. Changes in MHL were analyzed using multilevel models. Results Knowledge about mental health/illnesses, recognition of mental health state and intention to help peers/seek help when suffering from mental health problems, were significantly improved immediately and 3 months post-intervention. Conclusions Concise teacher-led programs administered in schools can have positive and lasting effects on MHL in pre-teens.